The Rhetoric of Empire in the Scottish Mission in North America, 1732–63. Issue 1 (April 2020) - Kelly, Jamie J.
Abstract : In 1755, William Robertson delivered a sermon before the Society in Scotland for Propagating Christian Knowledge, entitled The Situation of the World at the Time of Christ's Appearance …. He addresses British imperial expansion and its prospects for civil and moral improvement, while denouncing the moral decay manifest in the growth of slavery and exploitation of natives. Through advocating a considered balance between submission to revealed religious principles and the exercise of reason, Robertson stresses the necessity of both for promoting virtue and preventing vice. The SSPCK, an organisation dedicated to spreading 'reformed Christianity' as a catalyst of cultural progress (and thus the growth of virtue) among rural Scots and Natives in North America, was responding to a perceived lack of government commitment to this very task. Empire provided the framework for mission, yet the government's secular agenda often outweighed religious commitments. This article makes use of SSPCK sermons from the eighteenth century to trace the attitudes of Scottish churchmen and missionaries towards the institutions and motives driving empire, in a period when they too were among its most prominent agents. This will shed light on the Scottish church's developing views on empire, evangelism, race, improvability and the role of government.